2021
DOI: 10.2166/wcc.2021.138
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of smallholder farmers’ perception and adaptation response to climate change in the Olifants catchment, South Africa

Abstract: Climate change is expected to affect the livelihood of rural farmers in South Africa particularly the smallholder farmers, due to their overwhelming dependence on rain-fed agriculture. This study examines smallholder farmers' perception of climate change, the adaptation strategies adopted and factors that influences their adaptive decisions. The unit of data collection was household interview and focus group discussion. Climate data for the Olifants catchment (1986–2015) were also collected to validate farmers… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 34 publications
1
1
0
Order By: Relevance
“…According to Table 1, the study indicated that there were more male (60.5%) respondents as compared to 39.5% females in the study area (Table 1). The result was in line with (Obot et al, 2022a;Olabanji et al, 2021) who also showed in their study that smallholder farmers had more male than the female counterpart. This implied that the sex distribution of the farmers skewed towards male respondents as a result of the rigor involved in agricultural activities.…”
Section: Socio-economic Characteristics Of the Farmers Sexsupporting
confidence: 89%
See 1 more Smart Citation
“…According to Table 1, the study indicated that there were more male (60.5%) respondents as compared to 39.5% females in the study area (Table 1). The result was in line with (Obot et al, 2022a;Olabanji et al, 2021) who also showed in their study that smallholder farmers had more male than the female counterpart. This implied that the sex distribution of the farmers skewed towards male respondents as a result of the rigor involved in agricultural activities.…”
Section: Socio-economic Characteristics Of the Farmers Sexsupporting
confidence: 89%
“…Table 6 result also showed that a greater proportion (57.0%) of the respondents had Primary education, 16.5% had secondary education, 18.5% had no formal education and 8% had tertiary education. The result supported (Obot et al, 2022a;Olabanji et al, 2021) that most of the smallholder farmers had primary education which indicated that the farmers were open to learning and understanding the use of new technologies.…”
Section: Educational Qualificationmentioning
confidence: 53%
“…All else equal, this implies that on the average, the probability of older organizations and households experiencing no impact and small impacts is lower by 1.9% points and by 4.4% points respectively, compared with the younger farm- ers. In tandem with the findings of Olabanji et al [45] , age is an important household characteristic that has great implications on farmers' adaptive capacity. In fact, the effect of age may sometimes be location-specific and the expected relationship has been a subject of empirical debate because if the relationship appears negative (lowering the probability of being in a moderate or a high adaptive response category), such may be attributed to the risk-averse nature and less flexibility of the older farmers [46] .…”
Section: Factors Influencing the Levels Of Livelihoods Impacts Of Dro...mentioning
confidence: 56%
“…Smallholders' vulnerability manifests itself in who is at risk, highlighting a possible leverage point that might lead to changes in and/or reconsiderations of adaptation strategies planning and/or policy reforms (Eriksen et al, 2021;Olabanji et al, 2021;Kissinger et al, 2013).…”
Section: Introductionmentioning
confidence: 99%